2015
DOI: 10.1589/jpts.27.1467
|View full text |Cite
|
Sign up to set email alerts
|

Tai chi improves cognitive and physical function in the elderly: a randomized controlled trial

Abstract: [Purpose] To investigate the effect of Tai Chi on cognitive and physical function in the elderly. [Subjects and Methods] A randomized trial design was used. A total 150 subjects were enrolled and were divided into Tai Chi and control groups. Subjects in the Tai Chi group participated Tai Chi for 6 months, and subjects in the control group participated in other non-athletic activities. [Results] There were no differences between the groups in the one leg standing time with eyes open, left grip strength, or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 21 publications
5
60
0
3
Order By: Relevance
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…Because mind‐body exercise is a nonpharmacologic therapy, nearly all of the studies failed to blind the participants and personnel. The outcome assessments were blinded in 20 studies (62.5%) . Thirty studies (93.75%) had a low risk of attrition bias because most studies reported the dropout rate or represented detailed explanations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some traditional Chinese approaches may improve cognitive and physical function in the elderly 9,10. For example, Tai Chi Chuan (Tai Chi) is a traditional Chinese aerobic mind–body exercise with mild-to-moderate intensity that has recently become popular worldwide; it is appropriate for all ages 9.…”
Section: Introductionmentioning
confidence: 99%